Determination of human blood type using image processing techniques. (February 2017) - Ferraz, Ana; Carvalho, Vítor; Machado, José
Abstract: The undertaking of pre-transfusion tests is an essential task before the administration of a blood transfusion. It is through these tests that it is determined the blood profile compatible with the blood transfusion receiver. In certain emergency situations there is no time for performing the necessary tests with the available commercial systems and therefore it is administered the blood type O negative. This blood type is considered the universal donor, in the transfusion context, as it presents a lower risk of incompatibilities. However, even with the universal donor, transfusion reactions can occur in case of patients with different blood types. These incompatibilities can cause the death of the patient, depending on the severity of his or her health condition. This paper presents an electronic system and an interface application, able to perform all pre-transfusion tests quickly, easily, in safe conditions, and with high reliability, even in remote locations. To this end, the system is based on the plate test procedure and is of small dimensions being easy to carry. Another advantage of this system is its low cost that will be a factor of competition in the market. Moreover, the data acquisition is based on image processing techniques to obtain results, and it was developed using C# programming language. The user interface was developed with Xaml programming language as requirements of usability impose being compatible with a variety of platforms including computers, tablets, and smart phones.